Индукционный ускоритель электронов - бетатрон - Ананьев Л. М. (Госатомиздат, 1961)
Экземпляры: КХ (20120518) / Инвентарный номер: 294577 / Цена: 1.30 / Сис.шифр: 530.1 / Авт.знак: А 64 / ГРНТИ: 29 / ББК: 22.3